Assessing the efficacy of probiotics in augmenting bovine reproductive health: an integrated in vitro, in silico, and in vivo study - Gohil, Purva; Nanavati, Bhavya; Patel, Kajal; Suthar, Vishal; Joshi, Madhvi; Patil, Deepak B.; Joshi, Chaitanya G. (Frontiers in Microbiology, 2023)
The aim of this study was to isolate and characterize bovine-vaginal probiotics genotypically and phenotypically using in silico and evaluate their in vivo performance in buffaloes with endometritis. For the in vitro isolation and characterization, vaginal swabs were collected from 34 cows and 17 buffaloes, and 709 primary bacterial isolates with probiotic activity were obtained using MRS agar media. Two isolates Lactiplantibacillus plantarum KUGBRC (LPKUGBRC) and Pediococcus pentosaceus GBRCKU (PPGBRCKU) demonstrated optimum in vitro probiotic activities as compared to Lacticaseibacillus rhamnosus GG including, acid production, secretion of fatty acids and exopolysaccharide, cell surface hydrophobicity, self-aggregating and co-aggregating capacity with pathogens, anti-microbial activity and bacteriocin-like compounds against pathogens Escherichia coli and Staphylococcus aureus in cell-free supernatant and absence of hemolytic activity. Their phenotypic capacity was confirmed by analyzing the whole genome sequencing data and identifying genes and pathways associated with probiotic properties. These probiotic isolates have shown no virulence genes were discovered in their genomic study. In vivo study of 92 buffaloes suffering from clinical endometritis with purulent cervico-vaginal mucus (CVM) were randomly allocated 40 × 108 CFU/ml LPKUGBRC and PPGBRCKU and 40 ml Normal saline. The LPKUGBRC reduced the duration between administration of probiotic to induction of healthy estrus significantly. However, no effect was observed on pregnancy rate. These results suggest that LPKUGBRC and PPGBRCKU probiotic bacteria demonstrate probiotic efficiency and adaptability. Further sourced from the same niche as the targeted infection, they offer a distinct advantage in targeting the specific microbial population associated with endometritis. The findings of this study highlight the potential of LPKUGBRC and PPGBRCKU probiotics in treating endometritis and suggest further exploration of their clinical applications.